An Analysis of Teachers’ Questions in Teaching English During the COVID-19 Pandemic Era (A case of Teachers in SMP N 1 Soe) - Yabes Olbata; Ririn Fatmawati; Lesly Ndun (English Language and Education Spectrum, 2022)
The teaching and learning process in the classroom needs good communication between students and teachers. To make a good communication in the classroom, teacher is considered a crucial factor in creating the communication. Asking question is one way to have communication between teacher and students. But since the spread of the COVID-19, the teaching and learning process has change rapidly because students and teachers do not meet directly so the communication between students and teachers become less effective. This study aims to find out the kinds of teachers’ questions and the reasons for asking these questions. This study used qualitative descriptive design. The instruments used were observation and interview. The data of this study was collected through doing observation and interviews. The data of this study were analyzed by using Miles and Huberman’s model of analysis (Flow Model). The result of the study showed that during the pandemic era, the teachers mostly ask convergent questions (questions with short answers) and only ask divergent questions (questions with long answers) sometimes. While for the reasons, there are some reasons such stimulate and maintaining students’ interest, students to think and focus, clarifying students’ answers and encouraging students’ participation. Based on the result of the study, it can be concluded that the teachers tend to ask convergent questions that caused the students do not think critically during the pandemic era.